Historical Continuum in Bahamian Literary Thought - Sairsingh, A. Marie (International Journal of Bahamian Studies, 2018)
The works examined in this paper include Patrick Rahming’s “Slave Name”, written in the Bahamian post-independence era; Obediah Michael Smith’s “Wax Paper People” (2003), and Patricia Glinton-Meicholas’s “No Vacancy in Paradise” (2001). I place these works on a continuum of discursive engagement with weighty questions of ontology, existentiality, and the still profound deliberations on the issue of freedom, arguing that these works reflect an ongoing engagement with how history has shaped, and continues to shape the Bahamian identity, and the Afro-Bahamian identity more specifically.